Peran Brand Ambassador dalam Membangun Loyalitas Pelanggan pada Industri Kosmetik Lokal-Scarlett Whitening di Kota Bandung (Mansion: Management and Business on Kebangsaan, 2026)
Introduction: The skincare industry in Indonesia has witnessed exponential growth, leading to intense market competition among local brands. This study explores the critical role of marketing communication tools in securing consumer loyalty within a saturated market. Background Problems: Despite various promotional efforts, local brands face significant challenges in maintaining long-term retention due to high brand-switching behavior, leading to the research question: how do advertising and brand ambassadors collectively influence customer loyalty among Scarlett Whitening users in Central Bandung? Novelty: While previous studies have examined these variables independently, this research offers a unique integrative analysis of their simultaneous impact on a dominant local brand within a specific urban demographic, addressing a gap in empirical data regarding which factor acts as the primary driver of retention. Research Methods: A quantitative approach with descriptive and associative methods was employed, utilizing a sample of 99 respondents determined via the Slovin formula. Data were collected through structured questionnaires and analyzed using multiple linear regression and hypothesis testing (t-test and F-test) via SPSS 25. Finding/Results: The empirical findings demonstrate that both advertising and brand ambassadors have a positive and significant effect on customer loyalty, with a simultaneous contribution of 76.1%. Notably, the brand ambassador serves as a more dominant predictor of loyalty compared to conventional advertising. Conclusion: This study concludes that in the modern beauty industry, personification through credible figures is more effective in securing consumer commitment than information-heavy advertisements. The implications suggest that local firms must prioritize the selection of high-credibility ambassadors to maintain market stability.
Keywords: iklan; brand ambasador; loyalitas pelanggan